Subungual Exostosis Presenting as a Pyogenic Granuloma-like Lesion with Reactive Myofibroblastic Proliferation in Two Young Women - Rosanna Fox; Effie Katsarma; Nick Tiffin; Manuraj Singh (MDPI AG, 2022)
Subungual exostosis (SE) is a well-recognised benign proliferation of the distal phalanx most often seen in young adults and affecting the big toe. Possible triggers include previous trauma and chronic irritation or infection. We describe two atypical cases of SE in two young women presenting with pyogenic granuloma-like lesions clinically. Diagnostic biopsies were performed to confirm the diagnosis and excluded amelanotic melanoma. However, histology unexpectedly revealed reactive myofibroblastic proliferations mimicking nodular fasciitis overlying the SE. Given the atypical clinical presentation, the diagnosis was initially missed or not considered in both patients. They highlight two important points; the first is that SEs may present with pyogenic granuloma-like lesions clinically and that histological analysis is then required to exclude malignancy, particularly amelanotic melanoma. Secondly, that the histology will show a reactive myofibroblastic proliferation and if the sample is relatively superficial and pathologists are not aware of this potential reaction pattern, the underlying diagnosis of SE may be missed.